2016
DOI: 10.1212/wnl.0000000000002234
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya virus–associated encephalitis

Abstract: In the context of a large outbreak, CHIKV is a significant cause of CNS disease. As with other etiologies, CHIKV-associated encephalitis case distribution by age follows a U-shaped parabolic curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(86 citation statements)
references
References 37 publications
2
83
0
1
Order By: Relevance
“…Arthritogenic Old World alphaviruses also can cause encephalitis, but this occurs primarily in neonates (23). Between March 2005 and December 2006, a widespread outbreak of CHIKV occurred on the La Réunion Island in the Indian Ocean, infecting over one-third of the island population, causing at least 9 confirmed cases of neonatal encephalitis (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthritogenic Old World alphaviruses also can cause encephalitis, but this occurs primarily in neonates (23). Between March 2005 and December 2006, a widespread outbreak of CHIKV occurred on the La Réunion Island in the Indian Ocean, infecting over one-third of the island population, causing at least 9 confirmed cases of neonatal encephalitis (23).…”
Section: Introductionmentioning
confidence: 99%
“…Arthritogenic Old World alphaviruses also can cause encephalitis, but this occurs primarily in neonates (23). Between March 2005 and December 2006, a widespread outbreak of CHIKV occurred on the La Réunion Island in the Indian Ocean, infecting over one-third of the island population, causing at least 9 confirmed cases of neonatal encephalitis (23). Although some reports suggested that perinatal transmission of CHIKV may have occurred in the birth canal ( 24, 25 ), the presence of CHIKV RNA in the human placenta was confirmed in one case (26), although the cell type(s) targeted by the virus was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In up to 57% of the cases, musculoskeletal pain may persist for years234. Rarely, fatal cases occur and this is typically in patients with underlying conditions56789. The host’s innate immune response plays an important role in the control as well as the pathogenesis of CHIKV infection.…”
mentioning
confidence: 99%
“…Atypical presentations of CHIKV infection can involve almost every organ system, as seen in Table 2. Even though the most common extra-articular manifestations reported in the literature involve the nervous system 25– 27 and the eye 17 ; alterations in the gastrointestinal tract, liver 16 , kidney, muscles, mucous membranes and skin and hematologic cells have been evidenced, as well as in hemostasis and coagulation processes. Cardiovascular compromise is worthy of mentioning because of its usually fatal outcomes 10, 28 .…”
Section: Resultsmentioning
confidence: 99%